SURVEI KUALITAS LAYANAN INFORMASI OBAT DI PUSKESMAS PUTER DAN PUSKESMAS SEKELOA KOTA BANDUNG - Jelinna, Angghita
In Primary Health Care (Puskesmas), drug information service is conducted by Pharmacists to improve the achievement of optimal therapy. The aim of this study was to determine the quality of drug information service, the level of motivation and knowledge of respondents, and the type of drug information expected by patients to be given in two Primary Health Care in Bandung (Puskesmas Puter and Puskesmas Sekeloa). The study was a descriptive-observational study with cross-sectional-concurrent design from January to April 2017, using a validated questionnaire. Respondents were selected using purposive sampling technique. About 409 respondents were recruited at Puskesmas Puter and 374 respondents were recruited at Puskesmas Sekeloa. The quality of drug information service was analyzed using gap analysis on five service quality dimensions, while the respondents's compliance level were measured using Modified Morisky Scale (MMS). The results showed that overall perception of the quality of drug information service at Puskesmas Puter was 3.8 whereas Puskesmas Sekeloa was 3.7 from scale 5. The lowest quality of drug information service in both puskesmas was facility dimension. The quality of drug information service at Puskesmas Puter was not significantly different with Puskesmas Sekeloa (p = 0,700). The respondents from Puskesmas Puter and Puskesmas Sekeloa showed high level of motivation and knowledge which were 76,04% and 81,02%, respectively. Drug information such as drug strength, contraindication, drug interaction, warning during using medication / attention, and expiration date were given to about 2.5% of total respondents.